Chemoenzymatic route to stereodefined 2-(azidophenyl)oxazolines for click chemistry. (19th January 2021) - Monsen, Paige J.; Luzzio, Frederick A.
Graphical abstract: Highlights: Cyclization under Mild Conditions. Enzyme Hydrolysis under Aqueous Conditions. High ee's. Abstract: Aryl-substituted esters of a racemic diprotected 2-azido-1-alkanol were submitted to the Staudinger/aza-Wittig reaction in order to assess scope and establish conditions for their cyclization to the corresponding 2, 4, 5-trisubstituted oxazolines. Following the cyclization study, the (2 R, 3 R )-antipode of the azidoalkanol was obtained in high ee by incubation of the corresponding racemic azidoacetate with pig liver esterase (PLE). The p -nitrobenzoate of the enantioenriched 2-azido-1-alcohol was cyclized by the Staudinger/aza-Wittig to give the corresponding (4 R, 5 R )-disubstituted-2-(4-nitrophenyl) oxazoline. Selective reduction of the nitrophenyloxazoline to the corresponding aminophenyloxazoline using aluminum amalgam followed by direct azidation of the 2-(4-aminophenyl) moiety provided the corresponding (4 R, 5 R )-2-(4-azidophenyl) oxazoline derivative. The azidophenyl oxazoline was reacted with a proven click partner 4-ethynylfluorobenzene under copper/sodium ascorbate mediation to provide the click triazole product in high yield.